2010
DOI: 10.1007/s00276-009-0612-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological comparison between adolescent and adult lumbar pedicles using computerised tomography scanning

Abstract: Pedicle morphology in adolescent and adult population is different in all parameters, especially in males. Understanding of specific pedicle morphology for each group is imperative for safety in spinal procedures using pedicle route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“… 9 Sethi et al 21 reported individual anatomical variations in the pedicle axis, width and body habitus. Mughir et al 22 emphasized the critical role of pedicle morphology in spinal analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 9 Sethi et al 21 reported individual anatomical variations in the pedicle axis, width and body habitus. Mughir et al 22 emphasized the critical role of pedicle morphology in spinal analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study only included individuals aged above 50 years because Mughir et al 22 reported that pedicle morphology in young and adult population varied in all the parameters. We measured the LPT at the L5 level to obtain the most accurate measurements of thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of agerelated variations of the vertebral elements have largely been limited to the vertebral body and intervertebral discs (Allbrook, 1956;Ericksen, 1976Ericksen, , 1978aOda et al, 1988;Amonoo-Kuofi, 1991;Gocmen-Mas et al, 2010); in those studies, the vertebral elements were analyzed from an anthropological perspective rather than focusing on clinical or surgical applications. The literature contains very few reports about the vertebral pedicle, and those are limited to the lumbar region (Amonoo-Kuofi, 1995;Mughir et al, 2010).…”
Section: General and Intersegmental Observationsmentioning
confidence: 99%
“…The variations in the vertebral pedicle with respect to age have been studied by Amonoo-Kuofi (1995) and Mughir (2010). Their studies were limited to the lumbar region, where they found significant age-related variations in the horizontal and vertical diameters in the study groups (Amonoo-Kuofi, 1995;Mughir et al, 2010).…”
Section: General and Intersegmental Observationsmentioning
confidence: 99%
See 1 more Smart Citation